(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Public health plays a vital role in promoting and preserving the health of communities through comprehensive strategies aimed at preventing diseases, promoting health, and reducing health disparities. This abstract explores key strategies for prioritizing public health and achieving a healthier society. Emphasis is placed on prevention-focused healthcare, which involves shifting from reactive treatment to proactive prevention through initiatives such as vaccination programs, health education, and early disease detection. Additionally, health equity and social justice are essential principles in addressing underlying determinants of health and ensuring equitable access to healthcare services for all populations. Collaboration and partnerships across sectors and disciplines are highlighted as critical for addressing complex public health challenges and leveraging collective expertise and resources. Technological advancements, community engagement, and policy advocacy are identified as key enablers for promoting public health and advancing the goal of creating healthier communities.